Physicians' awareness and practice of home blood pressure measurement in Indonesia: Asia home blood pressure monitoring survey 2020 - Yuda Turana; Noriko Matsushita; Ebtehal Salman; Arieska Ann Soenarta; Vidya Gani Wijaya; Bambang Widyantoro; Eka Harmeiwaty; Rarsari Soerarso; Tunggul Diapari Situmorang (Faculty of Medicine, Universitas Trisakti, 2023)
BackgroundHypertension is a significant mortality risk factor. The knowledge and practice among physicians of hypertension management and home blood pressure monitoring (HBPM) in blood pressure control is important. We aimed to investigate the awareness and practice of HBPM among physicians in Indonesia after publishing of the local 2019 HBPM guidelines. MethodsThis was a cross-sectional study involving 611 physicians in Indonesia that was conducted between February and October 2020. The questionnaire covered awareness, knowledge, and practice of HBPM. ResultsA total of 330 male physicians (54.0%) aged 20-49 years participated in the survey. More than half were specialists (51.6%) and recommended HBPM to their patients with hypertension (89.0%). The awareness of HBPM benefits was substantial among the physicians; however, the knowledge of the home blood pressure (HBP) reference values of was low (7.9%). Around 54% of the respondents thought that the barriers to low recognition of HBPM are lack of HBPM guidelines or lack of understanding of HBPM among physicians. A considerable percentage provided instruction on HBPM that aligned with the local guidelines, but between 7.5-29.5% gave no instruction on HBPM. ConclusionMost physicians recommend HBPM, but there is still a lack of knowledge and attitude toward HBPM. In Indonesia, local HBPM guidelines were published in 2019, but have not yet sufficiently penetrated the country, therefore robust dissemination of the published HBPM guidelines is still needed. For efficient utilization of HBPM by physicians in clinical practice, developing user-friendly educational tools such as physicians’ pocket guide on HBPM instructions is essential.